Induksi Tunas dan Perakaran Bambu Kuning Bambusa vulgaris secara in vitro - Puji Astuti (Biogenesis: Jurnal Ilmiah Biologi, 2014)
An experiment to induction shoots and rooting of the shoot of yellow bamboo Bambusa vulgaris have been carried out. Single nodal segments with axillary buds were the starting material. After sterilization, nodal segments were directly inoculated on modified Murashige & Skoog (MS) medium, supplemented with cytokinin Benzylaminopurine (BAP) with various concentration (0,0 ppm, 0,5 ppm, 1,0 ppm and 2,0 ppm) and auxin Indole butyric acid (IBA) with various concentration (0,0 ppm, 2,5 ppm, and 5,0 ppm). The results of the experiment showed the combination BAP 1,0 ppm and IBA 2,5 ppm has effectively induced shoot multiplication. Meanwhile, the used BAP 2,0 ppm and IBA 2,5 ppm resulted in the best shoot elongation. On the other hand, rooting of the shoots in vitro have not been successful yet.Keywords: BAP, IBA, induction shoots and rooting, in vitro, yellow bamboo